Role of disorder on transport in boron-doped multiwalled carbon nanotubes - KRSTIC, VOJISLAV (The American Physical Society, 2003)
Electrical transport measurements on boron-doped multiwalled carbon nanotubes deposited on top of predefined electrode patterns have been performed. The temperature dependence of the conductance reveals through two-point configuration, the appearance of a zero-bias anomaly which was found to be not compatible with the existence of a Luttinger-liquid-like state in the doped multiwalled carbon nanotubes. The experimental findings indicate that, in order to properly interpret the charge transport properties of multiwalled carbon nanotubes, the doping as well as the energy window in which the experiments are performed are crucial points.
PUBLISHED
Keywords: Physics